IVORY Guidelines (Instructional Videos in Otorhinolaryngology by YO‐IFOS): A Consensus on Surgical Videos in Ear, Nose, and Throat. (17th August 2020) - Simon, François; Peer, Shazia; Michel, Justin; Bruce, Iain A.; Cherkes, Maryana; Denoyelle, Françoise; Fagan, Johannes J.; Harish, Muraleedharan; Hong, Paul; James, Adrian; Jia, Huan; Krishnan, P. Vijaya; et al.
Abstract : Objectives/Hypothesis: Otolaryngology instructional videos available online are often of poor quality. The objective of this article was to establish international consensus recommendations for the production of educational surgical videos in otolaryngology. Study Design: DELPHI survey. Methods: Twenty‐seven international respondents participated in this study from 12 countries. Consensus was reached after three rounds of questionnaires following the Delphi methodology. The proposals having reached the 80% agreement threshold in the third round were retained. Results: The main recommendations are as follows: 1) Ethics: patients must be anonymized and unrecognizable (apart from plastic surgery if necessary). A signed authorization must be obtained if the person is recognizable. 2) Technical aspects: videos should be edited and in high‐definition (HD) quality if possible. Narration or subtitles and didactic illustrations are recommended. 3) Case presentation: name of pathology and procedure must be specified; the case should be presented with relevant workup. 4) Surgery: surgical procedures should be divided into several distinct stages and include tips and pitfalls. Pathology should be shown if relevant. Key points should be detailed at the end of the procedure. 5) Organ‐specific: type of approach and bilateral audiometry should be specified in otology. Coronal plane computed tomography scans should be shown in endonasal surgery. It is recommended to show pre‐ and postoperative videos in voice surgery and preoperative drawings and photos of scars in plastic surgery, as well as the ventilation method in airway surgery. Conclusions: International recommendations have been determined to assist in the creation and standardization of educational surgical videos in otolaryngology and head and neck surgery. Level of Evidence: 5 Laryngoscope, 131:E732–E737, 2021